Asuhan Kebidanan Komprehensif Pada Ibu Hamil Bersalin Dengan Laserasi Derajat I, Nifas, Bayi Baru Lahir Pada Ny. “S” G3P2A0 Di Puskesmas Kalanganyar Kabupaten Lebak Tahun 2024 - Zulmi, Daini; Nelis April Yanti (Jurnal Obstretika Scientia, 2024)
in the world is around 443 per 100,000 KH, while the number of IMR in the world will reach 54 per 1000 KH in 2020. MMR in Lebak Regency reached 43 cases and IMR in Lebak Regency was around 30 cases in 2020. The government's effort for this case is the provision of essential and optimal health services. The purpose of this writing is expected to be able to provide comprehensive midwifery care (Pregnancy, Maternity, Postpartum, Newborn) to clients in a real way with the Varney midwifery management approach and SOAP documentation. Comprehensive case study method by taking pregnant women of 36 weeks gestational age until delivery assistance and monitoring of KF 1 to KF 4, and KN 1 to KN 3. The problems found in this case are ANC examination of physiological discomfort in the third trimester, preparation for lactation. The result was that the mother's discomfort was resolved and the mother's colostrum was present. In the process of labor there was a first degree perineal tear with active bleeding, a first degree perineal suture was performed and the laceration bleeding was no longer active. In the postpartum period it went well nd the client had done a 3-month injectable birth control. In the neonate examination, the baby was born with female sex, BW 3400 grams, PB 48 cm there were no defects and abnormalities in the baby.